Ego Dominus Tuus: Castiglione, Dante, and Yeats - Andrew Fitzsimons (ELOPE)
This paper explores the centrality of the poem “Ego Dominus Tuus” (1915) to Yeats’s thinking about the role of crisis and biographical self-fashioning in the creation of great art, and the significance of Italy and Italian examples in Yeats’s work. The vision of art that emerges in Yeats’s mature poetry, the doctrine of the mask and the anti-self, and the full articulation of his personal myth in A Vision (1925), are generated to a significant degree out of Yeats’s encounter with the courtly ideals of Baldassare Castiglione, which in turn informed his idiosyncratic, but for the development of his mature vision of art crucial, reading of Dante Alighieri. “Ego Dominus Tuus” is the poem in which the twin influences of Castiglione and Dante merge, and the poem which signals an imaginative fresh start for Yeats.